Procalcitonin Guided Antibiotic Therapy in Septic Critically Ill Patients Admitted to Critical Care Unit - Yahya Mohammed; Said Abd Al-Hameid; Ahmed El-Naggar (International Journal of Medical Arts, 2023)
Background: An important contributor to mortality and morbidity in intensive care unit [ICU] is sepsis. Increased mortality has been linked to putting off diagnosis and beginning the right treatment.Aim of the Study: In this investigation, the effectiveness of serum procalcitonin as a biomarker for septic critically unwell patients' antibiotic medication duration was be assessed.Patients and Methods: In this research, 50 individuals who met the inclusion criteria and required antibiotic therapy due to confirmed or strongly suspected bacterial infections were randomly divided into two groups, each of which had 25 patients. The other 25 patients received antibiotics in accordance with our ICU protocol [Group C-control group], while 25 patients received antibiotics in accordance with serum procalcitonin [PCT] guidance [Group P-PCT guided group].Results: PCT guidance enables a decrease in the dosage of antibiotics given to critically ill individuals with severe sepsis & septic shock. It was noticeable that the PCT group had much shorter periods of antibiotic therapy [mean of 4 days of less exposure to antibiotics and about 6 days shorter lengths of ICU stay]. The PCT group also had significantly fewer days spent in the hospital overall.Conclusion: An algorithm utilizing serial procalcitonin [PCT] measurements has been found to enable a more prudent utilization of antibiotics in individuals diagnosed with severe sepsis and septic shock. This approach effectively and safely reduces the duration of antibiotic exposure, as well as the length of ICU and hospital stays.